Market value calculation and the solution of circularity between value and the weighted average cost of capital WACC (2009)
Most finance textbooks present the Weighted Average Cost of Capital (WACC) calculation as: WACC = Kd×(1-T)×D% + Ke×E%, where Kd is the cost of debt before taxes, T is the tax rate, D% is the percentage of debt on total value, Ke is the cost of equity and E% is the percentage of equity on total value. All of them precise (but not with enough emphasis) that the values to calculate D% y E% are market values. Although they devote special space and thought to calculate Kd and Ke, little effort is made to the correct calculation of market values. This means that there are several points that are not sufficiently dealt with: Market values, location in time, occurrence of tax payments, WACC changes in time and the circularity in calculating WACC. The purpose of this note is to clear up these ideas, solve the circularity problem and emphasize in some ideas that usually are looked over. Also, some suggestions are presented on how to calculate, or estimate, the equity cost of capital. © 2009 Mackenzie Presbyterian University. All rights reserved.